Elijah of Buxton - Curtis, Christopher Paul. (New York : Scholastic Press, 2007)
Eleven-year-old Elijah Freeman, the first free-born child in Buxton, Canada--a haven for slaves fleeing the American South in 1859--uses his wits and skills to try to bring to justice the lying preacher who has stolen money that was to be used to buy a family's freedom.
Newbery Medal/Honor.
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), October 2009.
Book Links-starred, January 2008.
Booklist starred, September 2007.
Keywords: Blacks -- Canada -- Juvenile fiction; Liberty -- Juvenile fiction; Slavery -- Juvenile fiction; Blacks -- Canada -- Fiction; Freedom -- Fiction; Historical fiction; Slavery -- Fiction; Blacks -- Canada -- Fiction; Freedom -- Fiction; Historical fiction; Slavery -- Fiction; Canada -- History -- 1763-1867 -- Juvenile fiction; North Buxton (Ont.) -- History -- 19th century -- Juvenile fiction; Canada -- History -- 1763-1867 -- Fiction; North Buxton (Ont.) -- History -- 19th century -- Fiction; Canada -- History -- Fiction; North Buxton (Ont.) -- History -- Fiction